2016
DOI: 10.1111/nin.12149
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intention to help and helping behaviour in witnesses of bullying in nursing settings

Abstract: The role played by witnesses of bullying in nursing settings remains little studied, despite their potential relevance in explaining the onset and development of bullying. The objective of this study was to develop a model to account for witnesses' intention to help and helping behaviour in response to bullying in a nursing setting. Three hundred and thirty-seven witnesses completed self-report measures of variables predicting intention to help and helping behaviour. A full structural model was constructed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…While there is no universal definition of what constitutes workplace bullying, there is general agreement that it involves consistent negative behaviour over a prolonged period of time resulting in a power imbalance between target and perpetrator (Báez‐León et al., ; Einarsen, Hoel, Zapf, & Cooper, ). Workplace mobbing is a similar concept often investigated in the European and Scandinavian literature (Leymann, ).…”
Section: Bullying In Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no universal definition of what constitutes workplace bullying, there is general agreement that it involves consistent negative behaviour over a prolonged period of time resulting in a power imbalance between target and perpetrator (Báez‐León et al., ; Einarsen, Hoel, Zapf, & Cooper, ). Workplace mobbing is a similar concept often investigated in the European and Scandinavian literature (Leymann, ).…”
Section: Bullying In Nursingmentioning
confidence: 99%
“…In addition to research on the effects of bullying on victims, there is evidence that witnesses of bullying can also suffer negative consequences including a decrease in well‐being, an increase in stress (Vartia, ) and increased perceptions of injustice (Parzefall & Salin, ). While there is recognition that bystanders could potentially play an integral role in finding a solution to workplace bullying (Báez‐León, Moreno‐Jiménez, & Aguirre‐Camacho, ; D'Cruz & Noronha, ; Paull, Omari, & Standen, ), this group has to date received insufficient attention in research and public policy (Báez‐León et al., ). This paper aims to help address this gap by examining the responses of bystanders to bullying and the factors that influence their actions using the largest survey of nurses in Ireland to date.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Báez‐León et al. () found that bystanders hesitated to help targets for fear of retaliation, in this case the bystanders were afraid to cause further harm to the target due to the bully's aggressive personality. It is possible that this lack of obvious support from bystanders may have encouraged targets to resign from the company more quickly than they would have with effective peer support.…”
Section: Discussionmentioning
confidence: 99%
“…However, bystanders’ good intentions toward targets may be hindered by the possibility of negative outcomes for bystanders if they become involved (Báez‐León et al. ; Coyne et al. ; D'Cruz and Noronha ).…”
mentioning
confidence: 99%
“…For targeted employees, some of the main consequences are anxiety [9] and explosions of anger, irritation and aggressiveness [10] to name a few. Recently, the negative consequences of workplace bullying have been extended to witnesses [11] and perpetrators [12]; reinforcing the idea, that bullying is negative for all stakeholders in any organization.…”
Section: Introductionmentioning
confidence: 99%